2021
DOI: 10.1002/bio.4063
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazole‐based turn‐on fluorescence probe developed for highly specific and ultrasensitive detection of hypochlorite ions in living cells

Abstract: Hypochlorite (ClO−), as one of the active oxygen species (ROS), plays an essential role in the cellular defence system and organism immunity. In this paper, we successfully synthesized a new ‘turn‐on’ fluorescent probe BMF based on benzimidazole and characterized it by spectroscopic methods. The designed probe can quickly respond to ClO− with the obvious colour change from pink to colourless. Notably, the probe BMF exhibited almost no fluorescence, but showed strong fluorescence after adding ClO−, including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…From the research on optical detection of IEs from 2010 to 2021 ( Figure ), it can be found that the detection limits of hypochlorite, [ 41–57 ] perchlorate, [ 58–60 ] peroxide, [ 61–77 ] nitrate, [ 78–85 ] and nitrite [ 86–99 ] based on solution reaction are mostly between 10 −5 and 10 −9 M , and it is difficult to achieve higher sensitivity detection by merely optical probes designing. By combining the sensing probes with paper‐based [ 19,100–103 ] and hydrogel‐based [ 28,104–106 ] substrate and optical microscope device, the detection sensitivity has been greatly improved in 2020 and 2021 reaching a level of 10 −15 M. To better improve the detecting sensitivity, optical artificial olfactory system takes chemical sensor array as the detection modules of different IEs, as well as considering the automatic analyte collection with airflow and the ultrasensitive ecognition of optical signals has been explored from the design of different components.…”
Section: From Optical Chemical Sensor To Artificial Olfactory Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…From the research on optical detection of IEs from 2010 to 2021 ( Figure ), it can be found that the detection limits of hypochlorite, [ 41–57 ] perchlorate, [ 58–60 ] peroxide, [ 61–77 ] nitrate, [ 78–85 ] and nitrite [ 86–99 ] based on solution reaction are mostly between 10 −5 and 10 −9 M , and it is difficult to achieve higher sensitivity detection by merely optical probes designing. By combining the sensing probes with paper‐based [ 19,100–103 ] and hydrogel‐based [ 28,104–106 ] substrate and optical microscope device, the detection sensitivity has been greatly improved in 2020 and 2021 reaching a level of 10 −15 M. To better improve the detecting sensitivity, optical artificial olfactory system takes chemical sensor array as the detection modules of different IEs, as well as considering the automatic analyte collection with airflow and the ultrasensitive ecognition of optical signals has been explored from the design of different components.…”
Section: From Optical Chemical Sensor To Artificial Olfactory Systemmentioning
confidence: 99%
“…Researches on optical detection of hypochlorite, [ 41–57 ] perchlorate, [ 58–60 ] peroxide, [ 61–77 ] nitrate, [ 78–85 ] and nitrite [ 86–99 ] IEs from 2010 to 2021 and sensors with paper‐based [ 19,100–103 ] and hydrogel‐based [ 28,104–106 ] substrate and optical microscope device. The first Figure from left on bottom reproduced with permission.…”
Section: From Optical Chemical Sensor To Artificial Olfactory Systemmentioning
confidence: 99%
See 3 more Smart Citations